Dynamic Balanced Scorecard Approch for Government Organization Strategy Development : A Case Study of Education and Training Unit for Underground Mining (ETUUM) - Agung Prasojo, Hendris; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2017)
Abstract. Purpose- the purpose of this research is to analyze the development of Balanced Scorecard by strategy map that has been done in the Education and Training Unit for Underground Mining (ETUUM) using a system dynamic. Design/methodology - the use of system dynamic to develop the conceptual model from the balanced scorecard perspective which requires a variety of information that collected through observation, interview and document collection and secondary information. The conceptual model is intended to describe the condition of the organization as a virtual world that can provide a clearer picture of how the complexity of the organization. The conceptual model is also used as a tool to test the performance and strategies for the future. That it is important to note is that the model is the actual condition of the organization in the real world and focus on key variables even though some assumptions. In this study using four scenarios.Finding- to get sustainable business and the competitive advantages ETUUM strategy must include development in the learning and growth perspective (organization competency), the internal business process (NSPC and training program), as well as the customer perspective).Limitations– The research was done only in ETUUM organization and based on the hypothesis of literature and cases in ETUUM. The research can be spread more by analyze a whole of ETUUM Balanced Scorecard.Implications - research models can be developed further more to analyze the causal relationship between various indicators in the non-profit organization. With understand the causal relationship, the organization strategy more easy to decide, and the research can be developed in other government organizations, and comprehensively conducted from various Balanced Scorecard perspectives.Originality - this research is only a small part of the implementation of the Balanced Scorecard research, especially with system dynamic for government agencies are engaged training business in Indonesia. Keywords: Balanced Scorecard, dynamic system, organization strategy, cause and effect. Abstract. Purpose- the purpose of this research is to analyze the development of Balanced Scorecard by strategy map that has been done in the Education and Training Unit for Underground Mining (ETUUM) using a system dynamic. Design/methodology - the use of system dynamic to develop the conceptual model from the balanced scorecard perspective which requires a variety of information that collected through observation, interview and document collection and secondary information. The conceptual model is intended to describe the condition of the organization as a virtual world that can provide a clearer picture of how the complexity of the organization. The conceptual model is also used as a tool to test the performance and strategies for the future. That it is important to note is that the model is the actual condition of the organization in the real world and focus on key variables even though some assumptions. In this study using four scenarios.Finding- to get sustainable business and the competitive advantages ETUUM strategy must include development in the learning and growth perspective (organization competency), the internal business process (NSPC and training program), as well as the customer perspective).Limitations– The research was done only in ETUUM organization and based on the hypothesis of literature and cases in ETUUM. The research can be spread more by analyze a whole of ETUUM Balanced Scorecard.Implications - research models can be developed further more to analyze the causal relationship between various indicators in the non-profit organization. With understand the causal relationship, the organization strategy more easy to decide, and the research can be developed in other government organizations, and comprehensively conducted from various Balanced Scorecard perspectives.Originality - this research is only a small part of the implementation of the Balanced Scorecard research, especially with system dynamic for government agencies are engaged training business in Indonesia. Keywords: Balanced Scorecard, dynamic system, organization strategy, cause and effect.